Dynamic assessment of the tear film muco-aqueous and lipid layers using a novel tear film imager (TFI). Issue 1 (18th April 2019) - Segev, Fani; Geffen, Noa; Galor, Anat; Cohen, Yoel; Gefen, Raanan; Belkin, Avner; Arieli, Yoel; Epshtein, Shlomi; Oren, Anat; Harris, Alon
Abstract : Purpose: The objective of the study was to assess a new technology, the tear film imager (TFI), which can dynamically image the muco-aqueous and lipid layers. Methods: Prospective pilot case series of individuals with and without dry eye (DE). Two sequential images were obtained with the TFI. Measurements were assessed for reproducibility and compared with clinically derived DE metrics. Individuals were grouped into DE categories based on signs of DE. Results: 49 patients participated in the study with a mean age of 58.8 years (SD 15.9) and a female majority (69%). Reproducibility of the muco-aqueous layer thickness (MALT) was excellent (r=0.88). MALT measurements significantly correlated with the Schirmer score (r=0.31). Lipid break up time (LBUT) as measured by the TFI significantly correlated with the clinical measure of tear break up time (TBUT) (r=0.73). MALT and LBUT were significantly thinner and shorter, respectively, in the DE groups (mild–moderate and severe) compared with the control group. When comparing TFI parameters to clinically assessed signs, sensitivity of the device was 87% and specificity was 88%. Conclusion: The TFI is the first machine capable of reproducibly measuring muco-aqueous thickness in human subjects which correlates with Schirmer score. In parallel, it assesses other important aspects of tear film function which correlate with clinician assessed DE metrics.